Incentivising effort in governance of public hospitals: Development of a delegation-based alternative to activity-based remuneration. Issue 8 (August 2015) - Søgaard, Rikke; Kristensen, Søren Rud; Bech, Mickael
Highlights: Development of an alternative to activity-based reimbursement is examined. Hospital departments are delegated the authority to define local incentive schemes. We observe a high impact of the effort incentive in the form of innovation. We observe some incongruence between the new schemes and the principal's objectives. Abstract: This paper is a first examination of the development of an alternative to activity-based remuneration in public hospitals, which is currently being tested at nine hospital departments in a Danish region. The objective is to examine the process of delegating the authority of designing new incentive schemes from the principal (the regional government) to the agents (the hospital departments). We adopt a theoretical framework where, when deciding about delegation, the principal should trade off an initiative effect against the potential cost of loss of control. The initiative effect is evaluated by studying the development process and the resulting incentive schemes for each of the departments. Similarly, the potential cost of loss of control is evaluated by assessing the congruence between focus of the new incentive schemes and the principal's objectives. We observe a high impact of the effort incentive in the form of innovative and ambitious selection of projects by the agents, leading to nine very different solutions across departments. However, we also observe some incongruence between the principal's stated objectives and the revealed private interests of the agents. Although this is a baseline study involving high uncertainty about the future, the findings point at some issues with the delegation approach that could lead to inefficient outcomes.